Effect of pressure on the electronic structure of hcp Titanium - Jafari, M.; Jahandoost, A.; Vaezzadeh, M.; Zarifi, N. (Condensed Matter Physics, 2011)
The effect of pressure on the hexagonal close-packed structure of titanium is investigated. The lattice parameters of the equilibrium structure were determined in terms of the Gibbs free energy using the Epitaxial Bain Path method. When this process was repeated for several pressures, the effect of pressure on the lattice parameters was revealed. The calculated lattice parameters were in good agreement with the experimental and theoretical results. The effects of pressure on parameters depending on the electronic structure such as conductivity and resistivity in the ground state were also investigated up to 30 GPa using density functional theory. Дослiджено вплив тиску на гексагональну щiльно упаковану структуру титану.
Параметри ґратки визначалися в термiнах вiльної енергiї Ґiббса, використовуючи метод епiтаксiї шляхом Бейна. Коли цей процес повторювався для декiлькох тискiв,
було виявлено вплив тиску на параметри ґратки. Обчисленi параметри ґратки добре узгоджувалися iз теоретичними та експериментальними результатами. Вплив тиску на параметри, такi як провiднiсть та опiр в основному станi, в залежностi вiд електронної структури, також було дослiджено аж до 30 GPa, використовуючи теорiю функцiоналу густини.